INTROVERT PERSONALITY IN RAINBOW ROWELL'S FANGIRL - Umboh, Stefany I. S.; Mamentu, Agustine C.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research were to analyzed the introvert personality reflected in Rainbow Rowell’s Fangirl and also to explain the causes and effects of introvert personality reflected in Rainbow Rowell Fangirl. The method used in this research was descriptive qualitative. The collected data was then analyzed based on the theory taken by the researcher as a reference. In analyzing the data, the researcher used psychosocial theory. The results of this study indicate that introvert personality is found in Cath. Introvert personality also effects Cath to have low self-esteem, feel uncomfortable with her surroundings and difficulties in her social life. Cath's introvert personality be based on Erik Erikson's theory.